SAT0117 High uric acid as a risk factor for cardiovascular diseases in rheumatoid arthritis patients. (12th June 2018) - Al-Herz, A.; Aldei, A.; Saleh, K.; Al-Awadhi, A.; Al-Kandari, W.; Hasan, E.; Ghanem, A.; Hussain, M.; Nahar, E.; Abutiban, F.; Alenizi, A.; Ali, Y.; et al.
Abstract : Background: Rheumatoid arthritis (RA) patients have an increased risk of cardiovascular diseases (CVD). It is unclear whether an elevated serum uric acid (UA) further increases that risk. Objectives: We study CVD and their risk factors in association with UA in RA patients. Methods: Adult patients who satisfied the ACR classification criteria for RA from The Kuwait Registry for Rheumatic Diseases (KRRD) from four major hospitals were evaluated from February 2013 through May 2017. Patients with recorded UA were identified and CVD and their risk factors were studied in those patients. To optimize classifier number and prediction accuracy, hierarchical cluster analyses for multiple factors were performed, which indicated nine possible independent CVD risk factors. A binary logistic regression was conducted to examine their significant association with CVD and the independence of UA as a risk factor. Results: A total of 564 RA patients with available UA were identified, 353(62.6%) females. Mean age was 50.8±11.5 years and disease duration 10.5±2.9 years. Mean UA was 271±78 µmol/L. Of those patients, 31 (5.5%) were reported to have CVD. UA was significantly correlated to the presence of CVD (χ 2 =6.49, p =0.011). Logistic regression model indicated a 10% increase of CVD with every 10 µmol/L increase in UA. A correlation matrix between UA and other risk factors showed a significant association between high uric acid and a younger age at RA diagnosis (r=-0.262), hyperlipidemia (r=0.191) and diabetes mellitus (r=0.244). Conclusions: Our study suggests that UA may be an independent risk factor for CVD and is associated with the presence of other risk factors. UA should be measured and carefully approached in RA patients. Disclosure of Interest: None declared